1SWASP J010313.78+352903.7: A Totally Eclipsing Binary with Components in Poor Thermal Contact. (1st January 2023) - Wang, Zhihua; Zhu, Liying; Yuan, Kai
Abstract: We presented photometry for an EB-type totally eclipsing binary, 1SWASP J010313.78+352903.7, observed with the Xinglong 85 cm telescope on 2021 October 22. Light curves in five bands (including the TESS data) were analyzed by employing the Wilson–Devinney method. The photometric solutions show that it is a contact binary with a relatively low mass ratio ( q ≃ 0.28), relatively large fill-out factor ( f ≃ 40%) and large temperature difference (Δ T ≃ 1700 K). Max.I-Max.II is up to about 9% of variable light amplitude of the asymmetric light curves. It is well described by double-hot spots model on the surface of the cooler secondary. The two hot spots are both in growing and evolving. They may be caused by two different mechanics, i.e., magnetic stellar activity and mass transfer. The large temperature difference between the two contact components indicates that they share a non-thermal equilibrium common envelope.